What a difference trade makes: export activity and the flexibility of collective bargaining agreements - Wolf Dieter Heinbach; Stefanie Schröpfer (Institut für Angewandte Wirtschaftsforschung (IAW), 2007)
The prevalence of opening clauses in collective bargaining agreements may indicate a tendency to a higher decentralised wage settlement. Increasing competition on international product markets is assumed to be one reason for wage-setting decentralisation, whereas theoretical explanations focus currently on the change of production structure and the impact of exogenous shocks. Incorporating stylised facts about exporting firms, new trade models suggest a different way of adjustment to increasing competition depending on a firm's nature. While the most productive exporters expand into new markets, small, less productive non-exporters are threatened by import competition. Based on the model from Bernard et al. (2003), we apply the theoretical implications to explain why decentralisation in bargaining may arise. We examine in a second step whether small, less productive, non-exporting firms paying low average wages, possess a higher propensity to use opening clauses than more productive, large exporters with a high wage level. Based on IAB Establishment Data covering the German Manufacturing, our results indicate that firms exporting to EMU countries - but not exporters in general - have a lower propensity of using opening clauses than non-exporters. However, inconsistent with theory, slight evidence suggests a rising propensity with increasing firm size and increasing wage level.
Keywords: 330